Enhancing Fruit Orchard Establishment: A Multicriteria Approach for Plum Variety Selection - Nedeljković, Miroslav; Puška, Adis; Jeločnik, Marko; Božanić, Darko; Subić, Jonel; Štilić, Anđelka; Maksimović, Aleksandar (Yugoslav Journal of Operations Research; Vol 34 No 2 (2024), 2023)
This research is focused to identifying the most suitable plum variety for establishing a new orchard, aiming to achieve optimal outcomes. To accomplish this goal, multi-criteria decision-making model has been developed striving to support decision-making process. The gained results are based on experience of experts engaged in assessment of certain plum varieties. The analysis of collected expert ratings has involved mutual use of 3 methods, where the FUll COnsistency Method (FUCOM) and CRiteria Importance Through Intercriteria Correlation (CRITIC) methods were applied to determine the weights of selected criteria. The results of applying these methods demonstrated that the Maretability criterion is of highest importance. Besides, the fuzzy MARCOS method (Measurement Alternatives and Ranking according to Compromise Solution) has been applied to rank the plum varieties according to expert ratings. Derived results revealed that the “Čačanska rodna” and “Stanley” varieties were ranked as the most favorable, while the “Prezident” variety was assessed as the most unfavorable. Further, gained research outcomes were corroborated by the sensitivity analysis and results validation. This research contributes to improvement of fruit growing in BiH by previous adequate selection of available plum varieties towards the establishing of new orchards and yielding optimal outcomes.